Recent Trends in Dental Implant Materials and Surface Modifications: A Literature Review - Al-nafaai, Mohammad; Alsaleh, Dalal; Alazmi, Amjad; Alateeq, Amal; Alfayez, Yara; Alajwari, Hadeel; Alamri, Shatha Tareq; Alsahli, Nora; Alsaqer, Faisal (Journal of Posthumanism, 2025)
Introduction: The field of restorative dentistry has been transformed by the invention of dental implants, which provide a lasting remedy to the problem of tooth loss. The effectiveness of these implants is based on their capacity to achieve osseointegration with the surrounding bone tissue, integrating completely within the bone. Optimal osseointegration is attained through the use of biocompatible materials with certain modifications in the material surface that facilitate the adhesion, growth, and multiplication of bone cells, while preventing the colonization by bacteria.Aim of work: To critically examine recent advancements in dental implant materials and surface modification techniques, with a focus on their impact on osseointegration, antibacterial efficacy, and long-term clinical success. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Recent, Trends, Dental, Implant, Materials, and Surface Modifications. The search was restricted to publications from 2016 to 2025 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2025. The study was structured into various sections with specific headings in the discussion section.Conclusion: In conclusion, modern developments in the field of implant dentistry stem from a more integrated approach to the materials used in implants and their surface modification in order to improve the success rates of these implants. The field of implant dentistry continues to evolve as new strategies for surface engineering, antimicrobial treatments, and even different materials like zirconia are used. Further research and clinical investigations are still needed to make these changes reliable and routine.